Effectiveness of live attenuated influenza vaccine and inactivated influenza vaccine in children 2–17 years of age in 2013–2014 in the United States. Issue 1 (2nd January 2016) - Caspard, Herve; Gaglani, Manjusha; Clipper, Lydia; Belongia, Edward A.; McLean, Huong Q.; Griffin, Marie R.; Talbot, H. Keipp; Poehling, Katherine A.; Peters, Timothy R.; Veney, Naomi; Ambrose, Christopher S.
Highlights: This study assesses quadrivalent LAIV effectiveness in children. LAIV provided significant protection against B/Yamagata, but not A/H1N1pdm09. A new and more heat-stable A/H1N1pdm09 LAIV strain is proposed for 2015–2016. Abstract: Background: A postmarketing observational study was initiated to evaluate quadrivalent live attenuated influenza vaccine (LAIV) effectiveness in children aged 2–17 years in the United States. Methods: Children and adolescents aged 2–17 years seeking outpatient care for febrile acute respiratory illness <5 days duration were enrolled at 4 geographically diverse sites during the 2013–2014 influenza season. Nasal swabs were tested for influenza using reverse transcription polymerase chain reaction. Vaccination status was documented from medical records or immunization registries. Children who received ≥1 dose of influenza vaccine ≥14 days before study visit were considered vaccinated. Vaccine effectiveness (VE) was estimated as 100 × (1 − adjusted odds ratio), where the odds of interest are the odds of vaccine exposure among influenza cases and test-negative controls. Results: In total, 1033 children and adolescents were included in the analysis. Influenza was detected in 14% (145/1033) of all children, with 74% (108/145) of the influenza cases due to A/H1N1pdm09 strains, 21% (31) to influenza B, and 4% (6) to influenza H3N2. LAIV did not show significant effectiveness against A/H1N1pdm09 (VE 13% [95% CI: −55 to 51]) but was effective against B/Yamagata strains (82% [95% CI: 12–96]). Inactivated influenza vaccine was effective against A/H1N1pdm09 (74% [95% CI: 50–86]) and B/Yamagata (70% [95% CI: 18–89]). Conclusions: LAIV provided significant protection against B/Yamagata influenza but not against A/H1N1pdm09 in children aged 2–17 years in 2013–2014, resulting in a proposed change of the 2015–2016 formulation with a new and more heat-stable A/H1N1pdm09 LAIV strain.